The CARE Plus study – a whole-system intervention to improve quality of life of primary care patients with multimorbidity in areas of high socioeconomic deprivation: exploratory cluster randomised controlled trial and cost-utility analysis. Issue 1 (December 2016) - Mercer, Stewart; Fitzpatrick, Bridie; Guthrie, Bruce; Fenwick, Elisabeth; Grieve, Eleanor; Lawson, Kenny; Boyer, Nicki; McConnachie, Alex; Lloyd, Suzanne; O'Brien, Rosaleen; Watt, Graham; Wyke, Sally
Abstract Background Multimorbidity is common in deprived communities and reduces quality of life. Our aim was to evaluate a whole-system primary care-based complex intervention, called CARE Plus, to improve quality of life in multimorbid patients living in areas of very high deprivation. Methods We used a phase 2 exploratory cluster randomised controlled trial with eight general practices in Glasgow in very deprived areas that involved multimorbid patients aged 30–65 years. The intervention comprised structured longer consultations, relationship continuity, practitioner support, and self-management support. Control practices continued treatment as usual. Primary outcomes were quality of life (EQ-5D-5L utility scores) and well-being (W-BQ12; 3 domains). Cost-effectiveness from a health service perspective, engagement, and retention were assessed. Recruitment and baseline measurements occurred prior to randomisation. Blinding post-randomisation was not possible but outcome measurement and analysis were masked. Analyses were by intention to treat. Results Of 76 eligible practices contacted, 12 accepted, and eight were selected, randomised and participated for the duration of the trial. Of 225 eligible patients, 152 (68 %) participated and 67/76 (88 %) in each arm completed the 12-month assessment. Two patients died in the control group. CARE Plus significantly improved one domain of well-being (negative well-being), with an effect size of 0.33 (95 % confidence interval [CI] 0.11–0.55) at 12 months (p  = 0.0036). Positive well-being, energy, and general well-being (the combined score of the three components) were not significantly influenced by the intervention at 12 months. EQ-5D-5L area under the curve over the 12 months was higher in the CARE Plus group (p  = 0.002). The incremental cost in the CARE Plus group was £929 (95 % CI: £86–£1788) per participant with a gain in quality-adjusted life years of 0.076 (95 % CI: 0.028–0.124) over the 12 months of the trial, resulting in a cost-effectiveness ratio of £12, 224 per quality-adjusted life year gained. Modelling suggested that cost-effectiveness would continue. Conclusions It is feasible to conduct a high-quality cluster randomised control trial of a complex intervention with multimorbid patients in primary care in areas of very high deprivation. Enhancing primary care through a whole-system approach may be a cost-effective way to protect quality of life for multimorbid patients in deprived areas. Trial registration Trial registration:ISRCTN 34092919, assigned 14/1/2013.